The singularity is nearer : when we merge with Al - Kurzweil, Ray (Viking, 2024)
"This successor volume to The Singularity Is Near explores how technology will refashion the human race in the decades to come. In this entirely new book, Ray Kurzweil brings a fresh perspective to advances in the singularity-assessing the progress of many of his predictions and examining the novel advancements that, in the near future, will bring a revolution in knowledge and an expansion of human potential. Among the topics he discusses are rebuilding the world atom by atom with devices like nanobots; radical life extension beyond the current age limit of 120; reinventing intelligence by expanding biological capacity with nonbiological intelligence in the cloud; how life is improving with declines in poverty and violence; and the growth of technologies that can be applied to everything from clothes to building materials to growing human organs. He also considers the potential perils of biotechnology, nanotechnology, and artificial intelligence, including such topics as how AI will impact unemployment and the safety of autonomous cars, and "After Life" technology, which will reanimate people who have passed away through a combination of data and DNA"--